2007
DOI: 10.1073/pnas.0611600104
|View full text |Cite
|
Sign up to set email alerts
|

Chemical cues induce consumer-specific defenses in a bloom-forming marine phytoplankton

Abstract: Blooms of the phytoplankton Phaeocystis can comprise 85% of total production and generate major biogeochemical signals across broad oceanic regions. The success of Phaeocystis may result from its ability to change size by many orders of magnitude when it shifts from small cells of 4 -6 m to large colonies of up to 30,000 m in diameter. Single cells are consumed by ciliates but not copepods, whereas colonies are consumed by copepods but not ciliates. We demonstrate that chemical cues associated with each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
142
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 43 publications
(58 reference statements)
6
142
1
Order By: Relevance
“…Because pH was not measured in the present study in the flasks that contained the copepods and because of the obviously complex mechanisms by which it may affect DA production, we cannot totally exclude the possibility that pH, at least in part, had an impact on the DA levels. Long et al (2007) and Lundgren and Granéli (2010) found no differences in pH between the grazing treatments (A. tonsa and P. globosa) and controls (only P. globosa). In other similar induction experiments with copepodites and P. seriata, no significant changes in pH were found (N. Lundholm unpubl.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because pH was not measured in the present study in the flasks that contained the copepods and because of the obviously complex mechanisms by which it may affect DA production, we cannot totally exclude the possibility that pH, at least in part, had an impact on the DA levels. Long et al (2007) and Lundgren and Granéli (2010) found no differences in pH between the grazing treatments (A. tonsa and P. globosa) and controls (only P. globosa). In other similar induction experiments with copepodites and P. seriata, no significant changes in pH were found (N. Lundholm unpubl.).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assume that factors other than nutrients caused the increase in DA production. Levels of major inorganic nutrients have been measured in only a few studies, which have shown that chemicals released by the zooplankton induced either physiological or morphological responses in phytoplankton (Selander et al, 2006;Long et al, 2007;Lundgren and Granéli, 2010); however, the nutrients themselves have not been found to be the inductive factor in these studies. Selander et al (2006) assumed that the possible effect of excretions (ammonium) from A. tonsa to be negligible at saturating nutrient conditions in comparison to the effect of chemical cues from A. tonsa in enhancing PST production A. minutum.…”
Section: Discussionmentioning
confidence: 99%
“…Copepodamides represent, to our knowledge, the first characterized chemical cues that mediate interactions between marine zooplankton and their prey. Other abundant and bloomforming phytoplankton like the diatom Skeletonema marinoi and the prymnesiophyte Phaeocystis globosa also respond to unknown grazer cues by splitting colonies into smaller units that benefit from reduced losses to predators (3,4), suggesting that the ability to respond adaptively to grazer cues may be a common feature in bloom-forming algae.…”
Section: Discussionmentioning
confidence: 99%
“…A striking example is the chemical cues from zooplankton that provoke pivotal changes in prey traits. The responding phytoplankton induce toxin production, life history transitions, colony size changes, and alternations in swimming behavior to evade predation (3)(4)(5)(6)(7). The presence of zooplankton consequently modulates marine food webs in unforeseen ways beyond the direct consumption of prey.…”
mentioning
confidence: 99%
“…There are also chemical cues released by prey which cause a motile response in protists (Roberts et al 2011). Some phytoplankton species can recognize and react on chemicals re leased by predators by growing grazer resistant morphologies (Lürling & Von Elert 2001, Long et al 2007. It is unknown if chemicals released by ciliates can also have an effect on co-occurring species that are not their prey, predator or competitor.…”
Section: Known Secretion By Uronema Marinummentioning
confidence: 99%